Comparative Assessment of the WNT/β-Catenin Pathway, CacyBP/SIP, and the Immunoproteasome Subunit LMP7 in Various Histological Types of Renal Cell Carcinoma - Piotrowska, Żaneta; Niezgoda, Michał; Młynarczyk, Grzegorz; Acewicz, Magdalena; Kasacka, Irena (Frontiers in Oncology, 2020)
Objective: The Wnt/ß-catenin pathway plays an important role in pathogenesis of variety cancers. Most studies on changes in WNT/β-catenin pathway in RCC apply only to clear cell RCC, while there are no comparative assessments of this signalling pathway in various histological types of renal tumors in the available literature. Additionally, considering the close relationship between WNT/β-catenin signalling, CacyBP/SIP and proteasomal activity, it seemed worth comparing WNT/β-catenin pathway, CacyBP/SIP and LMP7 immunoproteasome subunit in human samples of clear cell, papillary and chromophobe RCC. Methods: Tests were performed on sections of three types of kidney tumors together with surrounding unchanged tissue fragments collected from 50 patients. Samples were divided into three groups depending on the histological type of cancer: clear cell, papillary and chromophobe RCC. Immunohistochemistry and PCR methods were used to identify WNT10A, Fzd5, β-catenin, GSK-3ß, CacyBP/SIP, LMP7 and gene expression. Results: Immunoreactivity and expression of WNT10A, Fzd5, β-catenin, GSK-3ß, CacyBP/SIP, LMP7 in clear cell RCC was markedly increased compared to non-cancerous kidney tissue. In papillary RCC, immunoreactivity and expression of WNT/β-catenin pathway, CacyBP/SIP, LMP7 was also increased compared to non-malignant kidneys, but it was less pronounced than in clear cell RCC. The least substantial increase in immunoreactivity and expression of WNT/β-catenin pathway, CacyBP/SIP, LMP7 was found in chromophobe RCC, compared to other RCC histological subtypes studied. Conclusions: Study results indicate an important role of WNT/β-catenin pathway, CacyBP/SIP and LMP7 in RCC carcinogenesis, and may indicate new aspects of pathomechanisms leading to differences in the biology of clear cell, papillary and chromophobe RCC.